Analysis of ball carrier head motion during a rugby union tackle without direct head contact: A case study. Issue 2 (April 2019) - Tierney, Gregory J; Gildea, Kevin; Krosshaug, Tron; Simms, Ciaran K
Rugby union players can be involved in many tackles per game. However, little is known of the regular head loading environment associated with tackling in rugby union. In particular, the magnitude and influencing factors for head kinematics during the tackle are poorly understood. Accordingly, the goal of this study was to measure head motion of a visually unaware ball carrier during a real game tackle to the upper trunk with no direct head contact, and compare the kinematics with previously reported concussive events. Model-Based Image-Matching was utilised to measure ball carrier head linear and angular velocities. Ball carrier componential maximum change in head angular velocities of 38.1, 20.6 and 13.5 rad/s were measured for the head local X (coronal plane), Y (sagittal plane) and Z (transverse plane) axes respectively. The combination of a high legal tackle height configuration and visually unaware ball carrier can lead to kinematics similar to average values previously reported for concussive direct head impacts.